Reinforcement of a Magnesium‐Ammonium‐Phosphate Cement with Calcium Phosphate Whiskers. Issue 12 (23rd September 2015) - Zorn, Katharina; Vorndran, Elke; Gbureck, Uwe; Müller, Frank A.
Abstract : Self‐setting resorbable phosphate cements are characterized by an excellent biocompatibility and bioactivity. However, poor mechanical properties restrict their application. Most studies which characterize phosphate cements mechanically focus on strength measurements. Examinations of mechanical reliability and facture toughness were hardly performed. In this study, calcium phosphate whisker‐reinforced magnesium‐ammonium‐phosphate (struvite) cements were examined at the whisker–matrix interface and the measured strength, reliability and toughness values were correlated to these observations. Moreover, the toughening mechanisms were evaluated. It was shown that whisker incorporation is not beneficial for material strength. It led to a strength decrease from 29.8 to 21.8 MPa by the incorporation of 15 vol% calcium‐deficient hydroxyapatite (CDHA) whiskers compared to the pure struvite cement. Weibull statistics and microstructural observations revealed that this is caused by the whisker–matrix interface, which acts as a flaw. In contrast with that, the reliability increases upon whisker incorporation. Furthermore, the critical stress intensity factor K IC as well as the work‐of‐fracture γwof increase from 0.52 to 0.60 MPam 1/2 and from 9.5 to 12.9 J/m² by the addition of 15 vol% CDHA whiskers compared to the original struvite cement. It was shown that whisker pull‐out and crack deflection are the main mechanisms responsible for this increase.